(untitled) (IAHS Medical Journal, 2022)
Background: Psorasis is a complex, chronic multifactorial inflammatory skin disease characterised by well demarcated, erythematous, scaly plaques on the extensor surface’s of the body and scalp. The purpose of the study to compare the efficacy and safety of systemic PUVA and UVB phototherapy in the management of chronic plaque psoriasis. Materials and methods: This comparative study was conducted at the Department of Dermatology and Venereology, Bangabandhu Memorial Hospital, USTC, Chattogram during the period of February 2018 to January 2019. Total 50 patients were selected in two groups, systemic PUVA (Psoralen and Ultraviolet A) (n=25) and UVB (Ultraviolet B) (n=25). Involvement of body surface by plaque psoriasis, erythema, scaling and induration were recorded in a 3 point scale before treatment and 14 days interval after giving PUVA or UVB and finally at 8th week. Results: Significant reduction of psoriasis at 1st follow up in systemic PUVA and UVB were 29.85 ± 8.95 and 31.93 ± 11.55 respectively and at 2nd follow up were 85.86 ± 7.33 and 28.48 ± 39.32 respectively. Significantly higher improvements was observed in systemic PUVA group than UVB group both at 1st and 2nd follow up. Conclusion: Therapeutic values of systemic PUVA is better than UVB phototherapy in the management of Chronic plaque psoriasis. IAHS Medical Journal Vol 4(1), June 2021; 47-50